ISLAMIC-CONTEXTUAL ENGLISH TEXTBOOK DEVELOPMENT TO STRENGTHEN TEACHER COMPETENCE - Syamsiah Depalina; Ali Jusri Pohan (JEE (Journal of English Education), 2026)
The lack of English textbooks that integrate Islamic values with contextual pedagogy remains a significant challenge in madrasah education, limiting teachers’ ability to deliver meaningful and character-oriented instruction. This study aims to develop an Islamic-contextual English textbook and examine its effectiveness in strengthening teacher competence. The research employed a Research and Development (R&D) approach using the ADDIE model, encompassing analysis, design, development, implementation, and evaluation stages. The participants involved 5 English teachers and 30 students in a madrasah setting, while three experts participated in the validation process. Data were collected through questionnaires, semi-structured interviews, classroom observations, expert validation sheets, and pre-test and post-test instruments. The questionnaire demonstrated high reliability with a Cronbach’s Alpha coefficient of α = 0.87. The findings revealed that the developed textbook achieved a validation score of 88%, categorized as “very valid” by expert reviewers. In terms of practicality, 87% of teachers reported that the textbook was easy to implement and effectively supported classroom instruction, while 85% of students found the materials engaging, relevant, and meaningful. The effectiveness analysis showed a significant improvement in learning outcomes, with the mean score increasing from 60.5 in the pre-test to 82.3 in the post-test. Furthermore, the normalized gain score reached 0.65, indicating a moderate improvement, while the effect size analysis yielded d = 0.80, which falls into the large effect category. The implementation of the textbook also contributed to strengthening teachers’ pedagogical and professional competence, particularly in integrating Islamic values and contextual learning approaches into English instruction. This study concludes that the development of an Islamic-contextual English textbook provides an innovative, valid, practical, and effective solution for improving teacher competence and supporting meaningful English language learning in Islamic educational contexts.